THE SIGNIFICANCE OF AN INTEGRATED APPROACH TO THE IMPLEMENTATION OF SPIRITUAL AND IDEOLOGICAL MECHANISMS (Scientific journal of the Fergana State University, 2023)
In this article, the author explores the importance of a comprehensive approach to the implementation of spiritual and ideological mechanisms in Uzbekistan. A set of measures aimed at socio-political and spiritual-ideological development of youth is covered.The study used sociological methods such as objectivity, historicality, comparative-historical, structural, structural-functional, analysis and synthesis, induction and deduction, document study, data processing, and grouping.The importance of a comprehensive approach to the consistent and effective implementation of state youth policy is as follows. Prevents various "gaps" in working with young people. This will ensure the interaction of society and the state, that is, the state must create appropriate conditions for young people to use their full potential and opportunities, and young people, in turn, must perform certain social functions